2018
DOI: 10.5194/amt-11-1481-2018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three aerosol chemical characterization techniques utilizing PTR-ToF-MS: a study on freshly formed and aged biogenic SOA

Abstract: Abstract. An intercomparison of different aerosol chemical characterization techniques has been performed as part of a chamber study of biogenic secondary organic aerosol (BSOA) formation and aging at the atmosphere simulation chamber SAPHIR (Simulation of Atmospheric PHotochemistry In a large Reaction chamber). Three different aerosol sampling techniques -the aerosol collection module (ACM), the chemical analysis of aerosol online (CHARON) and the collection thermal-desorption unit (TD) were connected to prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 45 publications
4
30
0
Order By: Relevance
“…Although based on a small selection of data, these numbers also broadly agree with earlier studies that have used other methods to try to quantify how large of a fraction of monoterpene-derived SOA consists of oligomeric compounds. It has been concluded that these compounds constitute around 50 % of SOA mass in laboratory setups (Baltensperger et al, 2005;Hall and Johnston, 2011;Putman et al, 2012), or even well above 50 % (Gao et al, 2004;Kolesar et al, 2015a), in general agreement with observations made on monoterpene-dominated ambient SOA (Kourtchev et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Although based on a small selection of data, these numbers also broadly agree with earlier studies that have used other methods to try to quantify how large of a fraction of monoterpene-derived SOA consists of oligomeric compounds. It has been concluded that these compounds constitute around 50 % of SOA mass in laboratory setups (Baltensperger et al, 2005;Hall and Johnston, 2011;Putman et al, 2012), or even well above 50 % (Gao et al, 2004;Kolesar et al, 2015a), in general agreement with observations made on monoterpene-dominated ambient SOA (Kourtchev et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Note that Eqs. (10) and (11) are analogous to methods presented by Hansel et al (1995) that calculate the volume mixing ratio of volatile organic compounds (VOCs) based on kinetic conditions in the drift tube.…”
Section: Retrieving the Transmissionmentioning
confidence: 99%
“…A number of previous studies have found that at least a part of POC from various sources is semi-volatile, including wood burning, gasoline and diesel vehicle exhausts and cooking (Lipsky and Robinson, 2006;Shrivastava et al, 2006;Robinson et al, 2007;Grieshop et al, 2009bGrieshop et al, , 20 2009cMay et al, 2013aMay et al, , 2013b. Moreover, a significant part of freshly formed SOC is semi-volatile and will contribute to the more volatile OC fraction desorbed at lower temperatures (Holzinger et al, 2010;Salo et al, 2011;Meusinger et al, 2017;Gkatzelis et al, 2018). The relative contributions from fossil and non-fossil sources to OC can be dependent on the volatility.…”
mentioning
confidence: 97%
“…It is likely that some of mvOC are of secondary origin, since SOC is formed in the atmosphere and subsequently condenses onto the aerosol particles (Hallquist et al, 2009;Jimenez et al, 2009). It has been shown that SOC formed in chambers 20 initially desorbed at relatively low temperatures (e.g., 200 °C) (Holzinger et al, 2010;Salo et al, 2011;Meusinger et al, 2017;Gkatzelis et al, 2018). However, there is also evidence that the formation of highly oxidized low-volatile compounds can occur in SOA formation (Ehn et al, 2014).…”
mentioning
confidence: 99%